P53 inhibits CRISPR–Cas9 engineering in human pluripotent stem cells. (July 2018) - Ihry, Robert; Worringer, Kathleen; Salick, Max; Frias, Elizabeth; Ho, Daniel; Theriault, Kraig; Kommineni, Sravya; Chen, Julie; Sondey, Marie; Ye, Chaoyang; Randhawa, Ranjit; Kulkarni, Tripti; et al.
Abstract CRISPR/Cas9 has revolutionized our ability to engineer genomes and conduct genome-wide screens in human cells1–3 . Whereas some cell types are amenable to genome engineering, genomes of human pluripotent stem cells (hPSCs) have been difficult to engineer, with reduced efficiencies relative to tumour cell lines or mouse embryonic stem cells3–13 . Here, using hPSC lines with stable integration of Cas9 or transient delivery of Cas9-ribonucleoproteins (RNPs), we achieved an average insertion or deletion (indel) efficiency greater than 80%. This high efficiency of indel generation revealed that double-strand breaks (DSBs) induced by Cas9 are toxic and kill most hPSCs. In previous studies, the toxicity of Cas9 in hPSCs was less apparent because of low transfection efficiency and subsequently low DSB induction3 . The toxic response to DSBs wasP53/TP53 -dependent, such that the efficiency of precise genome engineering in hPSCs with a wild-typeP53 gene was severely reduced. Our results indicate that Cas9 toxicity creates an obstacle to the high-throughput use of CRISPR/Cas9 for genome engineering and screening in hPSCs. Moreover, as hPSCs can acquireP53 mutations14, cell replacement therapies using CRISPR/Cas9-enginereed hPSCs should proceed with caution, and such engineered hPSCs should be monitored for P53 function. CRISPR–Cas9-induced DNA damage triggers p53 to limit the efficiency of gene editing in human pluripotent cells.